2015
DOI: 10.1177/0972150915601257
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Dynamic Relationship among Gold Price, Exchange Rate and Stock Markets: Evidence in Indian Context

Abstract: The purpose of research in this article is to investigate the relationship among gold prices, Bombay Stock Exchange’s Sensex, National Stock Exchange’s Standard and Poor’s (S&P) Financial Services LLC CNX NIFTY1 (S&P CNX NIFTY) and US dollar/Indian rupee (USD/INR) exchange rate for the period January 1998–April 2014. The relationship among these variables has been studied by applying vector error correction model (VECM) in order to check the long-run and short-run causality. Johansen cointegration test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 20 publications
3
17
0
Order By: Relevance
“…Similarly, Ali and Afzal (2012) affirm that the inflow of net capital from developed to emerging economies recorded a sharp decline from the beginning of the financial crisis. The evidence is in line with the Shiva and Sethi (2015) conclusion that financial markets are getting more integrated with attendant spill-over effect during a crisis period.…”
Section: Introductionsupporting
confidence: 88%
“…Similarly, Ali and Afzal (2012) affirm that the inflow of net capital from developed to emerging economies recorded a sharp decline from the beginning of the financial crisis. The evidence is in line with the Shiva and Sethi (2015) conclusion that financial markets are getting more integrated with attendant spill-over effect during a crisis period.…”
Section: Introductionsupporting
confidence: 88%
“…This research is also relevant for academicians to consider the period while finding out possible linkages between stock indexes, oil prices, gold prices, and exchange rate fluctuations. Another theoretical contribution is added to existing literature that there is the asymmetrical or nonlinear association between variables which are assumed to be linear by (Sahu et al, 2014;Shiva & Sethi, 2015;Tehreem, 2018;Keswani & Wadhwa, 2018;Neveen, 2018;Rajesh, 2019). Moreover, in existing literature few researchers have utilized arbitrage pricing theory to explain symmetrical connotations between macroeconomic fluctuations and stock indexes (Christofi et al, 1993;Günsel et al, 2009;Mollick & Nguyen, 2015;Saumya, 2012;Shahzad et al, 2017;Yan & Yang, 2016) while others have utilized EMH (Wickremasinghe, 2011;Hatemi-J, 2012;Singhania & Prakash, 2014;Othman et al, 2019).…”
Section: Discussion Theoretical and Practical Contributionmentioning
confidence: 99%
“…We have identified the following four most important research gaps in the existing literature. Firstly, in existing literature number of research articles have only explored linear linkages between stock indexes, exchange rate fluctuations, oil price volatilities, and gold prices by utilizing linear models like VECM (Badry, 2019;Keswani & Wadhwa, 2018;Neveen, 2018;Rajesh, 2019;Sahu et al, 2014;Shiva & Sethi, 2015), VAR (Areli Bermudez Delgado et al, 2018;Ghulam, 2018;Huang et al, 2018), ARDL modeling approach (Ho, 2018;Singhal et al, 2019) and limited efforts have been made to explore the asymmetrical impact of Exchange rates-Gold-Oil price volatility on stock indexes by using NARDL model by (Shin et al, 2014).…”
Section: Research Gapsmentioning
confidence: 99%
“…Recently, Adrangi, Chatrath, David-Christie, and Maitra (2014) studied the market co-movements among equity, commodity and exchange rates and found a very weak relationship between equity and commodity in India. Shiva and Sethi (2015) studied the dynamic relationship among gold prices, exchange rate and stock markets and found that gold prices unidirectional causes stock markets and exchange rates. In a study in a different context, Chakrabarty, De, and Bandyopadhyay (2015) applied wavelet based DCC-GARCH method in which they have shown that volatility spillover changes with the change of investment horizon.…”
Section: Literature Reviewmentioning
confidence: 99%